Tarling Music Virtual Concert Remediation Strategies in the COVID-19 Pandemic Era - Khaerudin Imawan; Heddy Shri Ahimsa-Putra; G.R. Lono Lastoro Simatupang (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
The Covid-19 pandemic is driving changes in how music concerts are produced, and tarling music is no exception. The government's policy, which included the implementation of Large-Scale Social Restrictions (PSBB) and the Enforcement of Restrictions on Community Activities (PPKPM), forced the event organizer, which used to hold entertainment stage concerts, including tarling music, to cease operations. Economically, the tarling musicians lose money because they are out of work for too long. Tarling musicians in Cirebon, West Java, are trying to break through in a variety of ways, including holding virtual music concerts. The purpose of this research is to uncover the practice of tarling music production in the era of the Covid-19 pandemic, as well as how tarling music agents adapt to their new habits regarding production methods through remediation strategies practiced through virtual and hybrid environments. This is a qualitative study that employs the paradigm of cultural materialism, as defined by Marvin Harris (1980a, p. 277), who believes that the material conditions of society determine human consciousness rather than the other way around. This research uses documentation study, observation, interviews, recording, and literature study as data collection methods. As a result, the Tarling music artist agency aggressively reforms the form of stage performance that is perceived as reality and presents it in the form of virtual and hybrid reality.